Calidad de servicio y fidelización de los clientes de a empresa Comercializadora San Juan SAC de la ciudad de Iquitos, julio 2021 - Ruiz Valles, Jhonh Kewin (2022)
The purpose of the investigation Quality of the Service and Loyalty of the Clients of the San Juan SAC trading Company of the city of Iquitos, March 2021, aims to determine the relationship between the quality of the service and the loyalty of the clients of the San Juan SAC trading company of the city of Iquitos, March 2021, it also considers as specific objectives to analyze the level of quality of service of its customers in each of its dimensions in the company San Juan SAC trading of the city of Iquitos, March 2021 and analyze the level of customer loyalty in each of its dimensions at the San Juan SAC trading company in the city of Iquitos, March 2021. The research is applied at a correlational level; The research concludes that there is a significant relationship between service quality and customer loyalty according to Spearman's Rho correlation coefficient of 0.781 and a bilateral significance of 0.000, which is less than 5% or 0.05, in the marketer San Juan SAC, march 2021.